Axonal transcription factors signal retrogradely in lesioned peripheral nerve - Ben-Yaakov, Keren; Blesch, Armin (The EMBO journal, 2012)
Retrograde axonal injury signalling stimulates cell body responses in lesioned peripheral neurons. The involvement of importins in retrograde transport suggests that transcription factors (TFs) might be directly involved in axonal injury signalling. Here, we show that multiple TFs are found in axons and associate with dynein in axoplasm from injured nerve. Biochemical and functional validation for one TF family establishes that axonal STAT3 is locally translated and activated upon injury, and is transported retrogradely with dynein and importin α5 to modulate survival of peripheral sensory neurons after injury. Hence, retrograde transport of TFs from axonal lesion sites provides a direct link between axon and nucleus.There is a Have you seen? (March 2012) associated with this Article.